USE OF STREAMING VR TECHNOLOGIES IN TEACHING THE TOPICS OF REDOX REACTIONS AND ELECTROLYSIS PROCESSES (Proceedings of International Educators Conference, 2024)
One of the most important tasks of the modern education system is to prepare students for a deep understanding of complex chemical processes and acquisition of practical skills. This article provides information on the use of streaming technologies and VR laboratories in the teaching of chemistry.